MASPEL - ORGANISASI PENGELOLAAN SAMPAH DESA ASTAPADA KECAMATAN TENGAH TANI KABUPATEN CIREBON - Atikah Nur Aisyah aghni; Nunung Nurhaeni; Assaf Zulkarnain; Akhmad Saidi; Lathifatul Jannah (Al Naqdu, 2021)
Every individu or group has a concern for the environment, the Astapada people are aware of togetherness in order to preserve the environment so that it can be passed to preserve the environment so that it can be passed on to future generations. In this study, respondents were selected directly by the researcher who was called the research target, namely 10 people. The results of this study indicate that the community cares about the environment is one way for the community to preserve nature and save the ecosystem of nature. to live a healthy life in the village of Astapada. And in addition to these advantages, there are also disadvantages where there are still people who are stupid and don't care about their environment, and the lack of cooperation between the village government and the sub-district so that the program does not run as desired